A microstrain measurement methodology applied to multiscale hydroforming of annealed ASTM 304 stainless steel sheet. (November 2015) - Emblom, William J; Aithal, Mitra; Jones, Richard J; Pesacreta, Thomas C; Glass, Gary A; Ibne Islam, Md FS; Wagner, Scott W
Meso- and microscale sheet metal forming represents new and attractive solutions to many manufacturing problems for product miniaturization. Larger organizations are utilizing commercially available microscale digital image correlation systems to measure the strains on these scales. The cost of these systems is preventing smaller research and development organizations from entering this challenging area or they are sacrificing the ability to determine strains and evaluate material behavior at the microscale. However, microscale strain grid measurement has the advantage over digital image correlation when the researchers wish to avoid polishing and etching the surface of the sheet metal to make the grain structure visible for digital image correlation and where tooling interferes with obtaining images of the workpiece in real time. This article evaluates the strain measurement and strains resulting from multiscale sheet metal hydroforming operations for annealed 0.2-mm-thick ASTM 304 stainless steel using a simple method for producing microscale grids that has been previously described. The gridding methodology was shown to be accurate with high repeatability. In addition, a strain grid measurement method using an optical microscope and digital camera is described and an error analysis was performed. Provided reasonable care is taken, the inherent error in undeformed parts is 0.76% of true strain for samples with 127 µm grids using the strain measurement system described. The maximum variation in the mesoscale and microscale strain measurement static bulge testing was ±2.4% and more typically ±1.3% of true strain. With care, the errors were reduced to less than 1% of strain. Microscale strains from sheet bulge hydroforming experiments for 11, 5, and 1 mm diameter dies are used to show that the strains measured are reasonable and consistent.